Comentário do Artigo - General Practice Routine Follow Up of Breast Cancer in Primary Care: Randomized Trial - Menke, Carlos Henrique; Biazús, Jorge Villanova; Xavier, Nilton Leite; Cavalheiro, José Antônio; Rabin, Eliane Goldberg; Bittelbrunn, Ana Cristina; Cericatto, Rodrigo; Bines, José; Carvalho, Heloisa de Andrade (Revista Brasileira de Cancerologia, 2000)
Comentário do artigo, Routine follow up of breast cancer in primary care: randomised trial BMJ; 313(7080):665–9, 1996. doi: https://doi.org/10.1136/bmj.313.7058.665